2006
DOI: 10.1080/02770900500498584
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Healthy Physical Activity in Asthma Patients

Abstract: Preliminary evidence indicates that asthma patients limit exercise and healthy lifestyle activities to avoid respiratory symptoms. This self-imposed decrease in activity, even among those with mild disease, may predispose to long-term general health risks. The objectives of this qualitative study were to determine patients' views about exercise and lifestyle activities and to determine if these views varied depending on asthma characteristics. During in-person interviews, 60 patients were asked open-ended ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
133
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 13 publications
5
133
0
8
Order By: Relevance
“…As far as peer support is concerned, the factor's association with VPA is sensible compared with previous research (14,16,19,(21)(22)(23)(24). Children and adolescents with asthma endeavour to be "normal" amongst peers (37) which may contribute to the perception of peer support by those with high level of PA and that boys participate in 0.55 hours more VPA each day than girls in the present study.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…As far as peer support is concerned, the factor's association with VPA is sensible compared with previous research (14,16,19,(21)(22)(23)(24). Children and adolescents with asthma endeavour to be "normal" amongst peers (37) which may contribute to the perception of peer support by those with high level of PA and that boys participate in 0.55 hours more VPA each day than girls in the present study.…”
Section: Resultsmentioning
confidence: 69%
“…Older subjects seems less sensible of parental support (19). Concerning parental restrictions to PA by fear of breathlessness in children and adolescents with asthma (15,16), one may also expect the association to be negative. Lack of negative significant association of parental support may thereby be interpreted as satisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 WBV training provides a means by which this requirement can be met as it provides health-related fitness benefits while reducing the non-compliance often encountered due to weather conditions, lack of motivation and work obligations. 4 This finding was substantiated in a statement that a short-term, supervised exercise protocol where the exercise scientist, health care professional or trainer has more or less direct influence and control over the intervention process, provided there is a fairly good adherence rate to the exercise programme. 5 CLBP has been defined as persistent or recurrent back pain experienced by an individual for a period longer than 3 months.…”
mentioning
confidence: 99%
“…Many clinical and experimental studies have suggested that decreased lung function can be attributed directly to airway inflammation and remodeling (2,3). In addition, decreased physical capacity is normally considered to be secondary to decreased lung function (4), and is strongly related to the psychosocial effects of asthma (5) and to peripheral skeletal muscle disuse (6). These secondary effects have been demonstrated in both asthmatic children and adults (7).…”
Section: Introductionmentioning
confidence: 99%